ANALYSIS OF THE UTILIZATION OF MOBILE COMMERCE IN MARKETING OF PROCESSED SOYBEAN PRODUCTS IN DADAPAN VILLAGE - Kasmi, Kasmi; Irviani, Rita; Falasarwa, Keyga (STMIK Pringsewu, 2025)
Soybean-based products such as tofu, tempeh, and tauco play a crucial role as affordable sources of plant-based protein for the community. However, micro-enterprises in Dadapan Village still face challenges in marketing, particularly limited market access, lack of promotion, and competition with similar products from other regions. Meanwhile, the development of mobile commerce (m-commerce) provides new opportunities to expand marketing networks through digital platforms. This study aims to analyze the strategies of soybean-based product entrepreneurs in utilizing mobile commerce, identify the challenges encountered, and evaluate its impact on market reach and business sustainability. Previous studies have mainly focused on traditional distribution channels and value-added analysis, leaving a research gap in exploring m-commerce adoption among rural micro-enterprises. This research employed a qualitative method with a case study approach, collecting data through interviews, observations, and documentation using purposive sampling. The results show that entrepreneurs primarily use applications such as WhatsApp, Facebook, and online marketplaces for marketing, which benefits them in terms of broader consumer reach, improved customer interaction, and product diversification. The main obstacles include limited digital literacy, distribution costs, and production capacity constraints. The study concludes that mobile commerce plays a significant role in enhancing the competitiveness of soybean-based micro-enterprises in rural areas, although continuous support in digital literacy and sustainable marketing strategies is still required.